Representasi Feminisme Liberal dalam Film Little Women karya Greta Gerwig - Salam, Amanda Riskia; Rullyanti, Merry; Astuty, Lina Tri (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to analyze the portrayal of liberal feminism in Greta Gerwig's film